Is inflation persistence intrinsic in industrial economies? - Andrew T. Levin; Jeremy M. Piger (European Central Bank (ECB), 2004)
We apply both classical and Bayesian econometric methods to characterize the dynamic behavior of inflation for twelve industrial countries over the period 1984-2003, using four different price indices for each country. In particular, we estimate a univariate autoregressive (AR) model for each series, and consider the possibility of a structural break at an unknown date. For many of these countries, we find strong evidence for a break in the intercept of the AR equation in the late 1980s or early 1990s. Allowing for a break in intercept, the inflation measures generally exhibit relatively low inflation persistence. Evidently, high inflation persistence is not an inherent characteristic of industrial economies.
Keywords: C11; C22; E31; 330; Bayesian econometrics; Inflation Dynamics; largest autoregressive root